2020
DOI: 10.3389/fpls.2020.00852
|View full text |Cite
|
Sign up to set email alerts
|

Phaeophyceaean (Brown Algal) Extracts Activate Plant Defense Systems in Arabidopsis thaliana Challenged With Phytophthora cinnamomi

Abstract: Seaweed extracts are important sources of plant biostimulants that boost agricultural productivity to meet current world demand. The ability of seaweed extracts based on either of the Phaeophyceaean species Ascophyllum nodosum or Durvillaea potatorum to enhance plant growth or suppress plant disease have recently been shown. However, very limited information is available on the mechanisms of suppression of plant disease by such extracts. In addition, there is no information on the ability of a combination of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 131 publications
(135 reference statements)
1
26
0
2
Order By: Relevance
“…Santaniello et al (2017) used another SWE to report the effects on photosynthetic performance in Arabidopsis. Islam et al (2020) reported SWE increased root growth in Arabidopsis. Given the effects of SWE reported across many different farming and growth environments using different crops, this implies their mode of action is conserved with an inherent plasticity when used as a foliar spray or soil application.…”
Section: The Effect Of Swe On Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Santaniello et al (2017) used another SWE to report the effects on photosynthetic performance in Arabidopsis. Islam et al (2020) reported SWE increased root growth in Arabidopsis. Given the effects of SWE reported across many different farming and growth environments using different crops, this implies their mode of action is conserved with an inherent plasticity when used as a foliar spray or soil application.…”
Section: The Effect Of Swe On Plantsmentioning
confidence: 99%
“…Studies using Arabidopsis, soybean and tomato plants have demonstrated that the application of SWE can improve plant tolerance to abiotic stresses such as drought, freezing and salt (Nair et al 2012;Martynenko et al 2016;Santaniello et al 2017;Goni et al 2018;Jithesh et al 2019). At a molecular level, laboratory studies have demonstrated that certain SWE have an intriguing capacity to activate plant defence response systems including the Systemic Acquired Resistance mechanism (Goni et al 2016;Islam et al 2020;Omidbakhshfard et al 2020). In addition, soil-applied SWE provide a wide range of nutrients for soil microbiota utilisation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment of the broccoli with the seaweed extract reduced the number of the plasmodia formed in the roots [ 144 ]. Islam et al [ 134 ] studied the protective effects of Seasol ® , ANE and an alkaline extract of Duvillaea potatorum on A. thaliana , before and after inoculation with the root pathogen Phytophthora cinnamomi, using a transcriptomics approach. Global transcriptomics analysis revealed that Seasol Commercial ® reduced the progression of P. cinnamomi by regulating proteolytic pathways, respiratory burst, and various defense-related responses.…”
Section: Seaweeds: Sources Of Extracts Used As Biostimulantsmentioning
confidence: 99%
“…Global transcriptomics analysis revealed that Seasol Commercial ® reduced the progression of P. cinnamomi by regulating proteolytic pathways, respiratory burst, and various defense-related responses. Overall, each seaweed extract acted differently, but all were successful in inducing plant defense-related genes [ 134 ]. The root drench treatment of 0.5% Dalgin ® (Sustainable Agro Solutions, Lleida, Spain), is another commercial extract prepared from A. nodosum that can significantly reduce the severity of a P. capsici infection of tomatoes by inducing the expression of several defense-related genes and also the activity of many oxidative enzymes [ 142 ].…”
Section: Seaweeds: Sources Of Extracts Used As Biostimulantsmentioning
confidence: 99%